Evaluación de tres niveles de caldo microbiológico en el rendimiento del cultivo organopónico de Marigold (Tagetes erecta), en la zona de Babahoyo - Santillán Castro, Fernando Fabian (2021)
It was held at the Faculty of Agricultural Sciences of the Technical University of Babahoyo, Los Ríos province; located at Km 7 1/2 of the Babahoyo - Montalvo road. Selected marigold seeds were used as experimental material. The treatments consisted of the doses of 2 L microbiological broth, 4 L microbiological broth, 6 L microbiological broth, 8 L microbiological broth, 10 L microbiological broth and control NPK. In the present experimental work, the Design called Complete Random Block was used, with six treatments (microbiological broth and control NPK) and four repetitions. To estimate the effects of the treatments, the Tukey test was performed at 5% probability. For the normal development of the crop, the necessary tasks were carried out, such as construction of drawers, placement of the substrate, planting, weed control, phytosanitary controls, fertilization, irrigation and harvesting. To determine the results, the data of plant height, number of branches, number of flower buds, yield and economic analysis were evaluated. Choosing five plants at random for each of the treatments. According to the results presented, it was determined that good results were achieved in the study of the microbiological broth, using the organoponic system; treatment T5 Microbiological broth applying ten liters obtained the highest height; The highest number of branches was obtained by the T4 Microbiological broth treatment applying eight liters; The treatments T2 microbiological broth with application of four liters, T3 microbiological broth with application of six liters, T4 microbiological broth with application of eight liters, T5 Microbiological broth with application of ten liters and in the same way the control of NPK, obtained the highest quantity of flower buds; the best performance was achieved with the application of treatment T3 Microbiological broth six liters, with a net benefit of $ 556.